Prayer, Purpose, and Expanding the Table of Possibility in Theological Education - Walton, Jonathan Lee (Theology today, 2025)
Dr. Jonathan Lee Walton's inaugural address as President of Princeton Theological Seminary presents a critical engagement with the narratives of religious decline, particularly in the context of American Protestantism. Challenging the cultural and class-based origins of “mainline” Protestant identity, Walton critiques the limitations of meritocratic structures that dominate both religious and societal frameworks. Drawing from the parable of the banquet in Luke 14, Walton argues for a reimagined theological and educational mission—one that expands the “table of possibility” by inviting those marginalized by traditional hierarchies. This address situates Princeton Seminary as a vital force in shaping a more inclusive, accessible theological education. Walton articulates the urgency of bridging the gap between historical privilege and contemporary spiritual hunger, highlighting the Seminary's role in cultivating moral imagination, advancing hybrid and flexible educational models, and addressing global challenges of justice and faith. Through this, he advocates for a Seminary that remains grounded in its mission while boldly adapting to serve a diverse and evolving world. This work contributes to ongoing theological discourse on institutional adaptation, ecclesiastical inclusivity, and the redefinition of religious leadership in the twenty-first century.